2′-Hydroxy flavanone derivatives as an inhibitors of pro-inflammatory mediators: Experimental and molecular docking studies. Issue 9 (1st May 2015) - Patel, Neeraj K.; Bairwa, Khemraj; Gangwal, Rahul; Jaiswal, Gaurav; Jachak, Sanjay M.; Sangamwar, Abhay T.; Bhutani, Kamlesh K.
Graphical abstract: The 2D interaction diagram of13 at the active site of TNF-α. Abstract: 2′-Hydroxy flavanone (1 ) was previously isolated from Mimosa pudica (L.) whole plant and was found to exhibit anti-inflammatory effects in vitro. There are also reports on anti-inflammatory properties of compounds bearing flavanone/chromone nucleus. Taking this into account, fourteen derivatives of 2′-hydroxy flavanone (1 ) were synthesized and evaluated against pro-inflammatory mediators (TNF-α, IL-1β and NO) in in vitro and in vivo models. Results directed that among the synthesized compounds, four derivatives (11 –14 ) showed profound inhibition of pro-inflammatory mediators as compared to the lead molecule. Further, 11 –14 demonstrated comparable anti-inflammatory activity with ibuprofen in carrageenan-induced rat paw edema assay and appreciable inhibition of lipopolysaccharide (LPS) induced pro-inflammatory mediators (TNF-α and IL-1β) in Sprague Dawley (SD) rats. The synthesized compounds were further subjected to molecular docking analysis and in silico prediction of pharmacokinetic properties.